PELATIHAN PEMASARAN ONLINE DAN PENGEMBANGAN APLIKASI BERBASIS ANDROID UNTUK PENGEMBANGAN KEWIRAUSAHAAN ALUMNI - Shinta Dhewi, Titis; Syihabudhin, Syihabudhin; Hariri Agus Prohimi, Afwan; Tri Kurniawan, Dediek (Transpublika Publisher, 2021)
Internet penetration in Indonesia has become an opportunity for business actors to increase their sales through online marketing. Especially in the field of marketing, the current digital era online marketing is becoming a very high trend among the public. In the midst of the development of digital technology, the team from Department of Management, Universitas Negeri Malang (UM) held training with a coaching approach for digital marketing. The target participants in this service are alumni of the management department on UM who own and are running a business. This training was carried out in two stages with the topics of (1) digital marketing and (2) digital business and digital transformation for its sustainability, the service team also developed an android-based application platform for the alumni of the management department on UM.